Optimizing high-resolution melting analysis for the detection of mutations of GPR30/GPER-1 in breast cancer - Aihara, Masamune; Yamamoto, Shigeru; Nishioka, Hiroko; Inoue, Yutaro; Hamano, Kimikazu; Oka, Masaaki; Mizukami, Yoichi (Gene, 2012)
G protein-coupled receptor 30/G protein estrogen receptor-1 (GPR30/GPER-1) is a novel membrane receptor for estrogen whose mRNA is expressed at high levels in estrogen-dependent cells such as breast cancer cell lines. However, mutations in GRP30 related to diseases remain unreported. To detect unknown mutations in the GPR30 open reading frame (ORF) quickly, the experimental conditions for high-resolution melting (HRM) analysis were examined for PCR primers, Taq polymerases, saturation DNA binding dyes, Mg2+ concentration, and normalized temperatures. Nine known SNPs and 13 artificial point mutations within the GPR30 ORF, as well as single nucleotide variants in DNA extracted from subjects with breast cancers were tested under the optimal experimental conditions. The combination of Expand High FidelityPLUS and SYTO9 in the presence of 2.0mM MgCl2 produced the best separation in melting curves of mutations in all regions of the GPR30 ORF. Under these experimental conditions, the mutations were clearly detected in both heterozygotes and homozygotes. HRM analysis of GPR30 using genomic DNA from subjects with breast cancers showed a novel single nucleotide variant, 111C>T in GPR30 and 4 known SNPs. The experimental conditions determined in this study for HRM analysis are useful for high throughput assays to detect unknown mutations within the GPR30 ORF. ► We developed an assay to detect mutations within the GPR30 ORF using HRM analysis. ► Nine known SNPs in the GPR30 ORF were clearly detected using this protocol. ► We detected a novel single nucleotide variant in the GPR30 ORF in breast cancer.